The impact of non-extraction orthodontic treatment on oral health-related quality of life: clear aligners versus fixed appliances—a randomized controlled trial. (8th April 2022) - Alfawal, Alaa M H; Burhan, Ahmad S; Mahmoud, Ghiath; Ajaj, Mowaffak A; Nawaya, Fehmieh R; Hanafi, Ibrahem
Summary: Objective: To assess the impact of clear aligner treatment on oral health-related quality of life (OHRQoL) compared to fixed appliance treatment. Trial design: Two-arm parallel group single-centre randomized controlled trial. Methods: Forty-four adult patients (8 males, 36 females) were randomly and equally assigned to either the fixed appliances group (FA) or the clear aligners group (CA). Randomization with an allocation ratio of 1:1 was performed by a researcher who is not involved in the study using a random sample table. Non-extraction cases were included in this study. Outcome measures were the OHRQoL of patients and the duration of orthodontic treatment. The OHRQoL of patients was assessed by the short-form Oral Health Impact Profile (OHIP-14) at the following assessment times: before the start of treatment (T0), 1 week (T1), 1 month (T2), 3 months (T3), and 6 months (T4) after the start of orthodontic treatment and post-treatment (T5). The assessor was blinded during outcomes assessment and statistical analysis. Results: Two hundred and eighteen patients were evaluated for eligibility, 44 of them fulfilled the inclusion criteria and were randomly allocated to treatment groups. None of the patients was lost to follow-up. Accordingly, the results of 44 patients were statically analysed. The total OHIP-14 score was not statistically different between the FA and the CA groups at T0 ( P = 0.91) and T5 ( P = 0.16), whereas it was significantly lower in the CA group as compared to the FA group at T1 (mean difference [MD] = 11.04, 95% CI 8.7 to 13.42, P < 0.001), T2 (MD = 6.00, 95% CI: 4.3 to 7.7, P < 0.001), T3 (MD = 3.37, 95% CI: 1.5 to 5, P < 0.01), and T4 (MD = 3.32, 95% CI: 1.7 to 4.9, P < 0.001). Treatment duration in the CA group was significantly shorter than in the FA group (MD = 4.18, 95% CI: 2.8 to 5.5, P < 0.001). No harms were observed. Limitations: The results were limited to the non-extraction treatment of mild to moderate crowding cases. Conclusions: Patients treated with clear aligners reported higher OHRQoL and shorter treatment duration as compared to those treated with fixed appliances. Trial registration: Retrospectively registered (DRKS-ID: DRKS00023977).